Belief and private religious practice as religious life commitment of an individual - Panmei Peter; Thiyam Rabikanta Singh (Lembaga Sembilan Tiga Community, 2022)
The present article study and explore on Rongmei tribe of Manipur. Particularly, it has chosen on Noney (Longmai) area, which is inhabited by Rongmei people. All the villagers are committed and worship to God as Baptist is the major denomination. So these make a commitment of an individual. The findings suggest that commitment of a male individual is religious life for them which will relate to belief and private religious practice. The method analyse here in this paper is linear regression and reliability scale. These include model summary, ANOVA, Residual statistics in linear regression and item statistics in scale reliability. Belief and private religious practice will be commitment of an individual when R square change, F change, sig. F change, mean square, F, sig, standard deviation, Range, maximum/minimum, variance is less than alpha value (0.05) or near to zero (1). This relation to alpha value will support to religious life commitment through belief and private religious practice. The questionnaires refer to BMMRS multidimensionality develops by Fetzer Institute (1999).